Development of Virtual Reality-Based Engine Room Simulator for Marine Engineering Training - Heri Sutanto; Imam Sutrisno (International Journal of Marine Engineering Innovation and Research, 2025)
Marine engineering education relies heavily on engine room simulators to build operational competence in a safe environment. However, conventional 2D or desktop-based simulators provide limited immersion and spatial awareness, which may reduce engagement and hinder the development of situational awareness and procedural memory. This paper presents the development of a Virtual Reality-Based Engine Room Simulator (VR-ERS) aimed at enhancing marine engineering training in accordance with STCW competencies. The proposed system combines a game engine–based 3D engine room model, real-time interaction with critical subsystems (fuel oil, cooling, lubrication, and electrical power), and head-mounted display (HMD)–based immersive visualization. A modular system architecture is proposed, including hardware (VR HMD, controllers, PC), software layers (3D modeling, interaction and physics, scenario engine), and a learning management interface for instructors. A training scenario framework is designed to cover normal operation, watchkeeping routines, and selected fault and emergency cases. A preliminary usability and acceptance study with marine engineering students is outlined using System Usability Scale (SUS) and Technology Acceptance Model (TAM) constructs. The development process demonstrates that VR-ERS can provide realistic engine room familiarization and procedural training, while offering flexibility for scenario authoring and future integration with learning analytics. The paper concludes with recommendations for full-scale validation studies comparing VR-ERS with conventional simulators in terms of learning outcomes, competency achievement, and cost-effectiveness.